Analysis of Innovation Strategies to Improve the Quality of Infrastructure in Public Organisation using the Technical Evaluation and Decision Square (TEDS) Method - Hafiz Rahman; Sri Oktavia; Yogi Irvanda (Jurnal Manajemen Indonesia, 2021)
This paper aims to analyze and discuss the implementation of innovative strategies in a public higher education institution in Indonesia. Analysis is undertaken by using Total Evaluation and Decision Square (TEDS) Method, which employs [a] Total Financial Management (TFM), [b] Total Content Management (TCM), [c] Total Process and Project Management (TPPM), and [d] Total Stakeholder Management (TSM) as the focus of analysis. The study is a qualitative study with the descriptive approach. Data and information were collected by using in-depth interview to the dean of the faculty and leaders of the department in the faculty as informants. Results of the interview were further analysed by using thematic analysis to get insights related to the topic of study. It can be inferred that the institution has already undertaken positive and beneficial innovation strategies. However, they are not effectively undertaken. This can be seen in the results of this study which show positive indicators in the parameters of Total Content Management (TCM), Total Process and Project Management (TPPM) and Total Stakeholder Management (TSM). The parameter of Total Financial Management (TFM), however, shows negative result in innovation strategy. The study reflects the actual condition of higher education institutions in Indonesia regarding institutional funding, and it further implies that the institution needs to be more innovative in finding suitable and reliable funding resources (apart from regular/yearly institutional budget as being provided by the Indonesian central government) to undertake its major tasks by law, which are [a] education, [b] research and development activities, as well as [c] the community development-empowerment activities. Keywords— TEDS method; total content management; total financial management; total process and project management; total stakeholder management